Efficient 2-Step Enzymatic Cascade for the Bioconversion of Oleuropein into Hydroxytyrosol - Giorgia Catinella; Silvia Donzella; Gigliola Borgonovo; Sabrina Dallavalle; Martina Letizia Contente; Andrea Pinto (MDPI AG, 2022)
Among the plant bioactive components, oleuropein (OLE) is the most abundant phenolic compound in all parts of olive trees (Olea europaea L.), particularly concentrated in olive leaves. It has been shown to present various remarkable biological actions, such as antimicrobial, antioxidant, anticancer and anti-inflammatory ones. On the other hand, hydroxytyrosol (HT), the main degradation product of OLE, is considered one of the most powerful antioxidant agents, with higher beneficial properties than the OLE parent compound. In this work, oleuropein was efficiently transformed into hydroxytyrosol using a 2-step biotransformation involving a thermo-halophilic β-glucosidase from Alicyclobacillus herbarius (Ahe), which gave the corresponding aglycone with complete conversion (>99%) and rapid reaction times (30 min), and an acyltransferase from Mycobacterium smegmatis (MsAcT), here employed for the first time for its hydrolytic activity. After cascade completion, hydroxytyrosol was obtained in excellent yield (>99% m.c., 96% isolated yield) in 24 h. Starting from a natural substrate and employing enzymatic approaches, the final hydroxytyrosol can be claimed and commercialized as natural too, thus increasing its market value.